Nonlinear vibration characteristics of shear deformable functionally graded curved panels with porosity including temperature effects. (May 2019) - Amir, Mohammad; Talha, Mohammad
Abstract: In this study, nonlinear thermo-elastic vibration characteristics of shear deformable functionally graded (FG) curved porous panels have been analyzed using the finite element method. The present formulation is based on the higher-order shear deformation nonlinear shell theory. The FG panels' material properties are varied continuously in the thickness direction by a simple power law distribution in terms of the constituents' volume fractions. The distribution of the porosity along the thickness direction is considered as even and uneven distribution. Comparison and convergence studies have been performed to validate the present nonlinear formulation. Parametric studies have been performed to study the effect of different influencing parameters on the frequency ratio of the curved FG panels, i.e., porosity, temperature rise, volume fraction indices, and side-to-thickness ratios. The benchmark solutions for the problems of large amplitude vibration characteristics have been accomplished with the present model. Highlights: Nonlinear thermo-elastic vibration analysis of functionally graded porous panels has been studied. Higher-order shear deformation theory has been applied. Even and uneven porosity distributions have been considered. Von-Karman type nonlinearity has been employed.